2022
DOI: 10.3390/antiox11020289
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Anti-Inflammatory Effects of Lipophilic Grape Seed Proanthocyanidin and Camellia Oil Combination in LPS-Stimulated RAW264.7 Cells

Abstract: Combination drug therapy has become an effective strategy to control inflammation. Lipophilic grape seed proanthocyanidin (LGSP) and camellia oil (CO) have been independently investigated to show anti-inflammatory effects, but their synergistic anti-inflammatory effects are unknown. The aim of this study was to investigate the synergistic anti-inflammatory effects of LGSP and CO. The anti-inflammatory activity of LGSP and CO individual or in combination on RAW264.7 cells was detected by MTT assay, Griess reage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…The positively correlation effects of anthocyanin, total phenolic, total flavonoid with their biological properties might be from synergistic effects. Previous study reported that the combination between phenolic compounds and anthocyanin showed synergistic anti-inflammation effects [ 38 ]. Moreover, the combination of anthocyanin and phenolic extract showed the synergistic effects on inhibited tumor growth and lung metastasis in breast cancer, MDA-MB-231 cells xenograft mice model [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The positively correlation effects of anthocyanin, total phenolic, total flavonoid with their biological properties might be from synergistic effects. Previous study reported that the combination between phenolic compounds and anthocyanin showed synergistic anti-inflammation effects [ 38 ]. Moreover, the combination of anthocyanin and phenolic extract showed the synergistic effects on inhibited tumor growth and lung metastasis in breast cancer, MDA-MB-231 cells xenograft mice model [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…This could be attributed to the anti-inflammatory properties of some of the constituents in grapeseed oil like proanthocyanidin. 4,7,8 Previous studies have shown that many botanical extracts including grapeseed oil contain bioactive constituents that can inhibit cyclooxygenase and lipoxygenase activities; thus, they can interfere or inhibit inflammatory mediators like prostaglandins, histamine, and serotonin. 4,7,8,[18][19][20] Optimizing delivery of these bioactive anti-inflammatory constituents was shown to alleviate signs of inflammation as shown by redness of the skin (erythema), swelling, edema, and pain.…”
Section: Discussionmentioning
confidence: 99%
“…The novel grapeseed oil‐loaded dermocosmetic nanoemulgel used in this study caused a significant reduction in erythema levels over the 12‐week study period compared to the placebo. This could be attributed to the anti‐inflammatory properties of some of the constituents in grapeseed oil like proanthocyanidin 4,7,8 . Previous studies have shown that many botanical extracts including grapeseed oil contain bioactive constituents that can inhibit cyclooxygenase and lipoxygenase activities; thus, they can interfere or inhibit inflammatory mediators like prostaglandins, histamine, and serotonin 4,7,8,18–20 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations